Pengaruh Kecukupan Konsumsi Zink dengan Kejadian Stunting: Studi Literatur - Septiana Purwandini; Dominikus Raditya Atmaka (Media Gizi Kesmas, 2023)
Background: Stunting is a condition where under five children' height not in accordance with standard according to age. This condition is caused by inadequate nutritional intake during the First 1000 Days of Life. Stunting in long term period can cause a decrease in productivity due to cognitive decline and brain development. One of the important nutritional intake to prevent stunting is zinc. Objectives: The purpose of this study was to determine the effect of zinc on the incidence of stunting in Indonesia. Methods: The research method in this article is a literature review on Google Scholar database with the keywords "The Relationship between Zinc and Stunting in Indonesia" in the last 10 years. Discussion: The results of review of 10 journals showed that there was an effect of zinc consumption on the incidence of stunting. This is due to the various functions of zinc in the body that are important for growth, including a role in the synthesis of growth hormone, helping bone lengthening, increasing the immune system, and increasing the sensitivity of the sense of taste, which increases appetite. Conclusions: Zinc is very important to prevent stunting, so consuming zinc in sufficient quantities in toddlers is highly recommended.